Validitas Dan Reliabilitas Instrumen Perhatian Dalam Belajar Pada Pembelajaran IPA Di SMP Negeri 34 Pekanbaru - Vera Rahmadhani; Suryanti; Nurkhairo Hidayati (Jurnal Ilmu Pendidikan Biologi dan IPA, 2026)
Learning attention plays an important role in students’ learning success; therefore, a valid and reliable instrument is required. This study aimed to analyze the validity and reliability of a learning attention instrument in science learning at SMP Negeri 34 Pekanbaru. A descriptive quantitative method was employed with a sample of 35 seventh-grade students. The instrument was a 20-item Likert-scale questionnaire. Validity was tested using the Pearson Product Moment correlation, while reliability was examined using Cronbach’s Alpha through SPSS 25. The results showed that 17 items were valid and the Cronbach’s Alpha value was 0.618, indicating sufficient reliability. Thus, the instrument is appropriate for use with revisions to several items.